2016
DOI: 10.1021/acs.jnatprod.6b00394
|View full text |Cite
|
Sign up to set email alerts
|

Hypocriols A–F, Heterodimeric Botryane Ethers from Hypocrea sp., an Insect-Associated Fungus

Abstract: The new heterodimeric botryane ethers hypocriols A-F (1-6) and the known compounds 4β-acetoxy-9β,10β,15α-trihydroxyprobotrydial (7), dihydrobotrydial (8), 10-oxodehydrodihydrobotrydial (9), and dehydrobotrydienol (10) were isolated from the solid cultures of an insect-associated fungus Hypocrea sp. The structures of 1-6 were elucidated primarily by NMR experiments. The absolute configuration of 1 was assigned using the modified Mosher method and electronic circular dichroism (ECD) calculations, whereas those f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…By the same protocol, the inhibitory effects of NO production in a dose dependent manner were observed in the LPS‐induced RAW24.7 cells treated by compounds 1 and 2 , respectively ( Figure , a ). Additional experiments indicated that compounds 1 and 2 down‐regulated the expression of proinflammatory cytokines including macrophage chemoattractant protein‐1 (MCP‐1), tumor necrosis factor (TNF‐ α ), and interleukin (IL‐6) in the LPS‐induced RAW264.7 cells after treatment with each compound at the doses of 10 and 1 μ m , respectively ( Figure , b – d ). In addition, a MTT assay revealed that compounds 1 and 2 did not reduce the cell viability of RAW264.7 macrophages up to a dose of 100 μ m , indicating that their inhibiting effects on LPS‐induced RAW24.7 cells were not due to cytotoxicity.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…By the same protocol, the inhibitory effects of NO production in a dose dependent manner were observed in the LPS‐induced RAW24.7 cells treated by compounds 1 and 2 , respectively ( Figure , a ). Additional experiments indicated that compounds 1 and 2 down‐regulated the expression of proinflammatory cytokines including macrophage chemoattractant protein‐1 (MCP‐1), tumor necrosis factor (TNF‐ α ), and interleukin (IL‐6) in the LPS‐induced RAW264.7 cells after treatment with each compound at the doses of 10 and 1 μ m , respectively ( Figure , b – d ). In addition, a MTT assay revealed that compounds 1 and 2 did not reduce the cell viability of RAW264.7 macrophages up to a dose of 100 μ m , indicating that their inhibiting effects on LPS‐induced RAW24.7 cells were not due to cytotoxicity.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, the peroxy bridge was oriented in the opposite face toward methylthiol group. The absolute configuration of C(2) was determined to be ( R ) based on the Δ δ ( R ) – ( S ) values calculated from ( R )‐ and ( S )‐MPA esters of 1 ( Figure ) by the Mosher method …”
Section: Resultsmentioning
confidence: 99%
“…1). Compounds 6-8 and 13-19 were identified as dehydrobotrydienol (6) [12], 12-hydroxydehydrobotrydienol (7) [12], hypocriol F (8) [13], 2,8-dihydroxy-3-methyl-9-oxoxanthene-1-carboxylic acid methyl ester (13) [14], preussochromone A (14) [15], preussochromone E (15) [15], roridin A (16) [16], roridin D (17) [17], roridin E (18) [18], and trichodermadienediol B (19) [19], respectively, by comparing their NMR, MS, and optical rotation data with literature values. The structure of 10 was identified as roseotoxin Z [20] by X-ray crystallographic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the new compounds 1-5, 9, and 11-12 were determined by extensive spectroscopic analysis. 13 C NMR (▶ Table 1), and HSQC data displayed four methyl signals, two oxygenated methylene signals at δ C/H 57.4/4.06 (d, J = 11.9 Hz) and 4.34 (d, J = 11.9 Hz) and δ C/H 71.0/ 3.29 (d, J = 10.7 Hz) and 3.33 (d, J = 10.7 Hz), and one oxygenated methine signal at δ C/H 68.4/3.63 (ddd, J = 11.6, 9.5, 3.6 Hz). The 1 H-1 H COSY correlations of H 3 -11-H-2-H 2 -3-H-4-H-5 (▶ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation